NANOSUSPENSION SOLIDIFICATION TECHNIQUE: EVALUATION OF HIGH SHEAR GRANULATION AS PER INDUSTRIAL PERSPECTIVE - DHANANJAY S. SINGARE; DR. GIRIRAJ T. KULKARNI; DR. K. GOWTHAMRAJAN (International Journal of Pharma and Bio Sciences, 2013)
The nanoparticles for pharmaceutical application are around now for over 35 years, but only few are commercialized. The major hurdle in its effective utilization is lack of basic understanding in nanosuspension solidification techniques. This study evaluates the efficacy of high shear granulation in converting nanosuspension to solid oral dosage form. Nanosuspension was manufactured using a media milling approach and was used as a binder for granulating two different blends containing varying ratios of soluble to insoluble filler. Results obtained by PSD and zeta potential confirmed the required nano characteristics of the nanosuspension. The granules characteristics revealed good flow property of the blends. Results demonstrated that, formulation F02 containing lower ratio of lactose to MCC yielded a tablet with low weight, thickness, disintegration time and similar dissolution rate as compared to formulation F01. The nanoparticulate tablets showed an increased dissolution velocity against the marketed preparation. The quantity and type of filler had no significant impact on the dissolution velocity.